2011
DOI: 10.1111/j.1524-475x.2011.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of closed incision management with negative pressure wound therapy (CIM): Hematoma/seroma and involvement of the lymphatic system

Abstract: The objective of this porcine study was to evaluate the effect of closed incision management with negative pressure wound therapy (CIM) on hematoma/seroma formation, fluid removal into the CIM canister, and involvement of the lymphatic system. In each swine (n = 8), two sets of ventral contralateral subcutaneous dead spaces with overlying sutured incisions were created. Stable isotope-labeled nanospheres were introduced into each subcutaneous dead space. Each contralateral incision was assigned to CIM (continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 19 publications
2
120
0
1
Order By: Relevance
“…However, with a mean reduction of 1·97 ml (day 5) and 1·44 ml (day 10), the clinical relevance is questionable. A larger effect was found in an animal study21 focusing on the effect of iNPWT treatment on lymph clearance. The authors found that 4 days of treatment reduced the quantity of haematoma/seroma by a mean(s.e.m.)…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, with a mean reduction of 1·97 ml (day 5) and 1·44 ml (day 10), the clinical relevance is questionable. A larger effect was found in an animal study21 focusing on the effect of iNPWT treatment on lymph clearance. The authors found that 4 days of treatment reduced the quantity of haematoma/seroma by a mean(s.e.m.)…”
Section: Discussionmentioning
confidence: 80%
“…The effect of iNPWT on wound exudate might be explained by the known biomechanical mechanisms that iNPWT applies to the tissue, such as a reduction in oedema, increased blood flow14, 19 and lymph clearance21. In contrast to the study on wound exudate (S. Karlakki et al ., personal communication), the study that investigated ‘days to dry wounds’33 as a primary outcome found no effect of iNPWT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It provides wound integrity, eliminating free spaces in the subcutaneous tissue between the layers of deep and superficial sutures, reducing the risk of hematoma formation (8). Kilpadi et Cunningham in an animal model evaluated significantly reduced incidence of hematoma formation in wounds treated using negative pressure therapy as compared to the control group, without collection of fluid in the container connected to the system, which can be explained by more extensive elimination from necrotic wound areas through the lymphatic system (9). Systems for the treatment of primarily closed wounds are composed of a tight dressing applied on the wound, overlapping on the skin around the wound, connected via a tube with a small pump generating negative pressure.…”
mentioning
confidence: 99%
“…Average evolution of wounds was 3.68 years, with an initial area of 31.76 cm 2 . .At the end of the treatment average wound size was 3.43 cm 2 . A global improvement in wound closure of 96.81% was observed after 49 days period.…”
Section: Duke Boot In the Management Of Chronic Leg Venous Ulcersmentioning
confidence: 97%